2017
DOI: 10.22603/ssrr.1.2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

The Recent Trend in Diagnosis and Treatment of Chronic Low Back Pain

Abstract: Abstract:Introduction: Development of evidence-based medicine has made a big change in diagnosis and treatment of chronic low back pain. The recent trend is assessed through a review of literature. Methods: The articles published in these 10 years are reviewed, and important points are examined. Results: In diagnosis, challenges for history taking and limit of imaging or clinical guidelines are revealed. In treatment, cognitive behavioral treatment and exercises are proved effective. Sleep disturbance has rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 95 publications
1
12
0
Order By: Relevance
“…In addition, we speculate the mechanism of the postural and symmetrical LBP improvement as being that the loads to the facet joint and disc bilaterally were improved because of the bilateral LEP relief by the decompression of the bilateral nerve root and cauda equina. Minimally invasive surgery particularly can also result in a favorable outcome for the treatment of patients with chronic LBP and spinal stenosis and our present results also support this finding [14]. By contrast, greater preoperative LBP results in a poorer surgical outcome after the decompression surgery [15].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, we speculate the mechanism of the postural and symmetrical LBP improvement as being that the loads to the facet joint and disc bilaterally were improved because of the bilateral LEP relief by the decompression of the bilateral nerve root and cauda equina. Minimally invasive surgery particularly can also result in a favorable outcome for the treatment of patients with chronic LBP and spinal stenosis and our present results also support this finding [14]. By contrast, greater preoperative LBP results in a poorer surgical outcome after the decompression surgery [15].…”
Section: Discussionsupporting
confidence: 84%
“… 22 Numerous previous studies have reported the relationships between musculoskeletal pain and LoS. 16 , 44 47 Recently, biopsychosocial factors were shown to be essential components associated with not only low back pain 48 , 49 but also knee pain, 50 , 51 because pain is affected by actual tissue damage and psychological experience. Psychometric properties have been reported to predict pain and disability outcomes not only in patients with low back pain 52 , 53 but also in patients with symptomatic knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain (LBP) is a common condition and one of the most serious physiological issues worldwide [1][2][3][4][5] . LBP can be caused by several factors in any part of the complex lower back system, such as the interconnected network of the spinal muscles, bones, discs, nerves, or tendons in the lumbar spine.…”
Section: Introductionmentioning
confidence: 99%